Psychophysiological responses to high-intensity interval training exercise over menstrual cycle phases: an exploratory study - Chavan, M.; Prado, R. C. R.; Ashley, C. D.; Kilpatrick, M. W. (Medicine & Science in Sports & Exercise, 2024)
Introduction Although there is potential for the menstrual cycle to impact psychophysiological responses to exercise, there has been a paucity of studies investigating this aspect, specifically in the context of high-intensity interval training (HIIT).